h-prime and h-semiprime ideals in $\Gamma_{N}$-semirings and Matrix Semiring $\left(\begin{array}{ll}R&\Gamma\\S&L\end{array}\right)$ - Sujit, Kumar Sardar; Bibhas, Chandra Saha (Armenian Journal of Mathematics, 2009)
n this paper we show that h-prime and h-semiprime ideals in a Nobusawa $\Gamma$-semiring are preserved by the functions $^{*'}(~)$, $^{+'}(~)$, $^{*}(~)$, $^{+}(~)$, $\Gamma (~)$ and S( ). This preservation property is then used to characterize h-prime and h-semiprime ideals in matrix semiring $\left(\begin{array}{ll} R & \Gamma \\ S & L \end{array} \right)$. Moreover, characterization theorems of h-regular and H-Noetherian $\Gamma-$semirings have been obtained.